Surviving the Struggle of COVID-19: Practical Recommendations for Pediatric/Adult Cardiology and Cardiac Surgical Programs in Resource-Limited Settings: a Review - Kevin Pilarczyk; Vinicius Nina; Lynn Boshkov; Barbara Ferdman; Emily A Farkas; Nicole Burnham; Renzo Cifuentes; Daniel Ntogwiachu; Aubyn Marath (Brazilian Journal of Cardiovascular Surgery, 2022)
ABSTRACT Introduction: The primary aim of this systematic review is to provide perioperative strategies to help restore or preserve cardiovascular services under threat from financial and personnel constraints imposed by the coronavirus disease 2019 (COVID-19) pandemic. Methods: The Medical Literature Analysis and Retrieval System Online, Excerpta Medica dataBASE, Cochrane Central Register of Controlled Trials/CCTR, and Google Scholar were systematically searched using the search terms “(cardiac OR cardiology OR cardiothoracic OR surgery) AND (COVID-19 or coronavirus OR SARS-CoV-2 OR 2019-nCoV OR 2019 novel coronavirus OR pandemic)”. Additionally, the webpages of relevant medical societies, including the World Federation Society of Anesthesiologists, the Cardiothoracic Surgery Network, and the Society of Thoracic Surgeons, were screened for relevant information. Results: Whereas cardiac surgery and cardiology practices were reduced by 50-75% during the pandemic, mortality of patients with COVID-19 increased significantly. Healthcare workers are among those at high risk of infection with COVID-19. Conclusion: Hospitals must provide maximum protective equipment and training on how to use it to healthcare workers for their mutual protection. Triage management of patients — which accounts for patient’s clinical status and risk-factor profile relatable to which services are available during the COVID-19 pandemic — is recommended. A strict reorganization of the hospital resources including preoperative, intraoperative, and postoperative detailed protective measures is necessary to reduce probability of vector contamination, to protect patients and the cardiovascular teams, and to permit safe resumption of cardiological and cardiac surgical activity.